Certified Programs and Proofs Third International Conference, CPP 2013, Melbourne, VIC, Australia, December 11-13, 2013, Proceedings - Gonthier, Georges.; Norrish, Michael. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Certified Programs and Proofs, CPP 2013, colocated with APLAS 2013 held in Melbourne, Australia, in December 2013. The 18 revised regular papers presented together with 1 invited lecture were carefully reviewed and selected from 39 submissions. The papers are organized in topical sections on code verification, elegant proofs, proof libraries, certified transformations and security.